How work life balance and performance measurement are related to the employee performance during COVID 19 - Dr. Sameh Abdelhay,; Prof, Dr. Attiea Abdelhay,; Dr. Noor Fareen Abdul Rahman, (RES MILITARIS, 2023)
In the time of the COVID-19 pandemic, this study evaluates the impact of performance assessment on the employee's performance, as well as the ramification of work-life balance on employee performance. In this study, the population is the public hospital employees in the UAE. The total number of samples taken was 350. The sample method utilized is the side probability method, with proportional random sampling technique. The researcher to the factor analysis method preferred the principal component analysis with Varimax rotation method. Using spearman correlation after translating the data from categorical to numerical, the researcher examined the degree of correlation and strength of relationship between performance assessment and employee performance. In addition, the researcher used a spearman test to investigate the correlation between performance management strategies and employee performance based on demographics. Research finding shows that performance measurement has a major influence on employee during COVID 19 and that companies need to pay attention to the issues of work-life balance to keep employees inspired and optimize employee productivity, particularly during the COVID-19 pandemic through online work.